Efficacy and safety of fecal microbiota transplantation for chronic insomnia in adults: a real world study - Fang, Haiming; Yao, Tingting; Li, Wanli; Pan, Na; Xu, Hang; Zhao, Qian; Su, Yuan; Xiong, Kangwei; Wang, Jiajia (Frontiers in Microbiology, 2023)
Objective: To assess the efficacy and safety of fecal microbiota transplantation (FMT) for adult chronic insomnia. Methods: Patients treated with FMT for chronic diseases were divided into chronic insomnia and non-insomnia group. The primary endpoint was the efficacy of FMT for insomnia four weeks after treatment, the secondary endpoints included the impacts of FMT on anxiety, depression, health-related quality of life, gut microbiota, and adverse events associated with FMT. Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI) were utilized to assess the efficacy of FMT on insomnia, self-rating anxiety/depression scale (Zung Self-Rating Anxiety Scale (SAS) , Zung Self-Rating Depression Scale (SDS) ) was employed to evaluate anxiety and depression. Quality of life was evaluated by SF-36. 16S rRNA sequencing was employed to analyze the gut microbiota and correlation analysis was performed. Results: Forty patients met the inclusion criteria and seven were excluded. 33 patients were enrolled and stratified into chronic insomnia group (N=17) and non-insomnia group (N=16). Compared to baseline, FMT significantly ameliorated the ISI (17.31±5.12 vs 5.38 ± 5.99), PSQI (14.56±2.13 vs 6.63±4.67), SAS(54.25±8.90 vs 43.68±10.64) and SDS (57.43±10.96 vs 50.68±15.27) score and quality of life of chronic insomnia patients. 76.47% (13/17) of insomnia patients achieved the primary endpoints. In chronic insomnia patients, the relative abundance of Eggerthella marked enhanced at baseline, while the relative abundance of Lactobacillus, Bifidobacterium, Turicibacter, Anaerostipes, and Eisenbergiella significantly increased after FMT treatment, the latter positive correlated with the efficacy of FMT. Encouragingly, FMT also improved the sleep quality of non-insomnia patients. Conclusion: Eggerthella may potentially serve as a distinctive genus associated with chronic insomnia. FMT maybe a novel treatment option for adults with chronic insomnia and provide an alternative to traditional treatments for insomnia. The effects were positive correlated with the augmentation of probiotics, such as Bifidobacterium, Lactobacillus, Turicibacter, and Fusobacterium.